INTEGRATION OF FACE RECOGNITION TO ACCESS THE DOOR (International Journal of Food and Nutritional Sciences, 2022)
This project aims to develop a face recognition system for door access control. Face recognition technology has gained significant attention due to its non-intrusive and convenient nature. The system employs deep learning techniques to accurately identify individuals based on their facial features. It incorporates a camera to capture facial images, a trained neural network to process and recognize faces, and a secure access control mechanism. The system's feasibility, security, and user-friendliness are evaluated. This integration offers a more efficient and secure means of door access, reducing the reliance on traditional methods like keys or access cards. The results suggest that face recognition technology can be a reliable and convenient solution for door access control, potentially revolutionizing the field of security and access management.